1991
DOI: 10.1002/1097-4679(199103)47:2<205::aid-jclp2270470205>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

A factor analysis of the DSM-III post-traumatic stress disorder criteria

Abstract: The authors factor analyzed DSM‐III‐based post‐traumatic stress disorder symptom ratings made on 131 Vietnam‐veteran PTSD patients. Five factors – termed Intrusive Thoughts and Their Effects, Increased Arousal, Impoverished Relationships, Guilt, and Cognitive Interference – emerged. The factor structure gave more support to Laufer, Brett and Gallops' conceptualization of PTSD than to the Horowitz, DSM‐III, or DSM‐III‐R systems. It also generated suggestions for future editions of the diagnostic manual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Early studies of PTSD structure used exploratory factor analysis (EFA), revealing a variety of underlying factor models including two (Taylor, Kuch, Koch, Crockett, & Passey, 1998;Simms & Watson, 1999), three (Foa, Riggs, & Gershuny, 1995), four (Sack, Seeley, & Clarke, 1997), and five factors (Watson et al, 1991). Researchers hypothesized that different models emerged for any of several possible reasons, such as the use of different measures (Palmieri et al, 2007), different samples (Norris et al, 2001;Shevlin & Elklit, 2012), and limitations of EFA as a technique itself (Yufik & Simms, 2010).…”
Section: Structural Studies Of Ptsdmentioning
confidence: 99%
“…Early studies of PTSD structure used exploratory factor analysis (EFA), revealing a variety of underlying factor models including two (Taylor, Kuch, Koch, Crockett, & Passey, 1998;Simms & Watson, 1999), three (Foa, Riggs, & Gershuny, 1995), four (Sack, Seeley, & Clarke, 1997), and five factors (Watson et al, 1991). Researchers hypothesized that different models emerged for any of several possible reasons, such as the use of different measures (Palmieri et al, 2007), different samples (Norris et al, 2001;Shevlin & Elklit, 2012), and limitations of EFA as a technique itself (Yufik & Simms, 2010).…”
Section: Structural Studies Of Ptsdmentioning
confidence: 99%
“…Guilt for surviving a traumatic event or for having acted is frequently reported (Joseph et al, 1997) and must be accounted for in the evaluation. As a symptom of PTSD, guilt was removed during the revision of the diagnostic criteria; it had been observed to appear as a separate entity in factor analytic studies of DSM-III-R criteria (American Psychiatric Association, 1987;Silver and Iacono, 1984;Watson et al, 1991). The presence of symptom clusters qualitatively different from guilt, shame or other affective states can be clearly identi ed using recent diagnostic criteria.…”
mentioning
confidence: 99%
“…Older factor analytic studies of PTSD have not supported the current DSM-IV organization of the clusters. These studies have found factors representing reexperiencing or intrusion, withdrawal, numbing or impoverished interpersonal relationships, and guilt or "selfpersecution" (Keane et al, 1988;King & King, 1994;Silver & Iacono, 1984;Watson et al, 1991).Although there is wide variation in the number and types of factors identified in these studies, they have all included a factor representing intrusion or arousal and a separate numbing, withdrawal, or avoidance factor. A 1998 confirmatory factor analysis study by King, Leskin, King, and Weathers (1998) tested a variety of nested models of PTSD in a sample of 524 treatment-seeking male veterans.…”
mentioning
confidence: 99%
“…Previous studies of the structure of PTSD have generally focused on veteran populations. The majority predated the publication of the DSM-IV and generally did not focus exclusively on the 17 items now included as PTSD criteria in the DSM-IV (Keane, Caddell, & Taylor, 1988;King & King, 1994;McFall, Smith, McKay, & Tarver, 1990;Silver & Iacono, 1984;Watson et al, 1991). Older factor analytic studies of PTSD have not supported the current DSM-IV organization of the clusters.…”
mentioning
confidence: 99%
See 1 more Smart Citation